THE EDUCATION OF AKHLAK IN THE ALGHAZALY AND IBNU MASKAWAIH'S PERSPECTIVE (Comparative Study of Educational Thought in Kitab Ihya”Ulumuddin Dan Kitab Tahdzib Al-Akhlaq Wa Tathir Al-A’raq) - Husenudin Ahmadi; Nana Jumhana; Erdi Rujikartawi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
This qualitative research was conducted by the writer with a background on the importance of moral behavior (noble character) for humanity through the figure of the Prophet Muhammad. who has great morals (khulukun adzim). The formulation of the problem in this study is